Enhancing innovative work behavior through laissez-faire leadership, entrepreneurial self-efficacy, and work engagement: The moderating role of organizational citizenship behavior in 4-star hotels - Triono, Triono; Kusmaningtyas, Amiartuti; Halik, Abdul (Edelweiss Applied Science and Technology, 2024)
In a competitive environment, an employee is required to be able to demonstrate innovative work behavior in order to provide an advantage to the organization. Innovative work behavior is a complex behavior of employees who generate, introduce and implement innovative ideas (AlEssa & Durugbo, 2022). Thus, Innovative Work Behavior offers the ability to maintain competitive advantage and maintain organizational sustainability. They can create unique experiences for consumers, develop attractive new services, and improve operational efficiency. That is why individual innovative behavior in the workplace has the highest importance in achieving innovation at the organizational level. This study replicates and modifies research that has been conducted by (Gemeda & Lee, 2020), (Wei et al., 2020), (Khan et al., 2020) and the variables used are adjusted to the object of the study. The variables in question include: Laissez-faire leadership style, Entrepreneurial self-efficacy, Work engagement, Organizational citizenship behavior, Innovative work behavior. The argument related to the variables used in this study is that employees are willing to behave innovatively at work if they have a leader with a Laissez-faire leadership style, which gives freedom to everyone they lead in doing work or in making decisions (Avolio, B. J., & Bass, 2001). The population in this study were permanent employees of 5 4-star hotels in Lubuklinggau, South Sumatra with a total of 300 people. The sample determination used the Slovin formula, with an error rate of 5% so that a sample of 171 respondents was obtained. This study uses data analysis that is adjusted to the research pattern and the variables studied. The model used in this study is a causality model and to test the hypothesis proposed in this study, the analysis technique used is SEM (Structural Equation Modeling) which is operated through the AMOS version 26 program. SEM is a multivariate statistical technique which is a combination of factor analysis and regression analysis (correlation), which aims to test the relationships between variables in a model, both between indicators and their constructs, or the relationship between constructs. The results of the study concluded that Laissez-faire leadership has no significant effect on the work engagement of employees of 4-Star Hotels in Lubuklinggau, South Sumatra, Entrepreneurial self-efficacy has a significant positive effect on the work engagement of employees of 4-Star Hotels in Lubuklinggau, South Sumatra, Laissez-faire leadership style has an effect on the innovative work behavior of employees of 4-Star Hotels in Lubuklinggau, South Sumatra, Entrepreneurial self-efficacy has an effect on the innovative work behavior of employees of 4-Star Hotels in Lubuklinggau, South Sumatra, Work engagement has a negative insignificant effect on the innovative work behavior of employees of 4-Star Hotels in Lubuklinggau, South Sumatra, Organizational citizenship behavior moderates the effect of Work engagement on the innovative work behavior of employees of 4-Star Hotels in Lubuklinggau, South Sumatra.